Thymomas and Thymic Carcinomas: Prognostic Factors and Multimodal Management - Moser, Bernhard; Scharitzer, Margit; Hacker, Stefan; Ankersmit, Jan; Matilla, Jose Ramon; Lang, Georg; Aigner, Clemens; Taghavi, Shahrokh; Klepetko, Walter (The Thoracic and Cardiovascular Surgeon, 2014)
Background Thymomas and thymic carcinomas are rare malignant tumors. We report the experience with the resection and multimodal treatment at a single department in Central Europe in the years 2001 to 2010. Objective We sought to determine prognostic factors in this patient population.Methods A 10-year retrospective analysis of 84 resections on 72 patients for thymomas/thymic carcinomas or their recurrences was performed.Results Patients admitted to a single thoracic surgery center presented with Masaoka–Koga stage I (29.2%), II (43.1%), III (13.9%), and IV (13.9%). In approximately 88.9% of cases, a complete resection could be reached. Using overall survival as an outcome measure, the 5-year survival rate was 87%. Of all the cases presented, 9.7% cases showed tumor recurrence and 6.9% cases showed tumor progression. There was decreased survival rate with increasing Masaoka–Koga stage (p = 0.017) and incomplete resection (p < 0.001).Conclusion Completeness of resection and Masaoka–Koga stage were significant prognostic factors. Multidisciplinary treatments of patients with thymoma or thymic carcinoma result in good patient care, and global efforts with larger number of patients are needed to elucidate more about the biology, diagnosis, and treatment of these tumors.
Keywords: mediastinal tumor; thymus; mediastinum; chemotherapy; radiation therapy; surgery/incisions